Hajj crowd simulation based on intelligent agent - Mulyana, Willy Wahyu; Gunawan, Teddy Surya (2010)
Hajj ritual involves many pilgrims from more than one hundred countries with more than two million people every year. This paper presents simulation of the hajj crowd based on the development on intelligent agent. The intelligent agent is able to adapt and show rational behavior, to recognize the environment, and to do action. The concept of intelligent agent is applied to the individual pilgrim to build the crowd behavior. The results showed that hajj crowd simulation is able to demonstrate more realistic pilgrims’ behavior for three hajj activities, i.e. thawaf, sa'i, and jumrah. Moreover, subjective evaluation revealed that the developed system can be used for training the pilgrim before they perform actual activities.